2010
DOI: 10.1016/j.ophtha.2009.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of CD30+ Lymphoid Proliferations in the Eyelid

Abstract: Purpose To report the clinicopathologic features of three patients with CD30+ lymphoid proliferations of the eyelid. Design Retrospective case series. Participants Patients with cutaneous CD30+ lymphoproliferative lesions of the eyelid. Methods Three patients with CD30+ non-mycosis fungoides T cell lymphoid infiltrates of the eyelid were identified. The histories, clinical findings, pathologic features including immunohistochemical staining, treatments and outcomes were reviewed and compared. Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…7 Cutaneous periorbital and oral mucosal involvement is rare but has been reported; ocular mucosal involvement specifically has not been reported. 8,9 Some data implicate activation of the JAK-STAT pathway with the development of LyP. A recent study of 12 patients with CD30 + lymphoproliferative disorders, including 6 LyP patients, suggested that an increased frequency of activating mutations in the JAK-STAT pathway may contribute to the pathogenesis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Cutaneous periorbital and oral mucosal involvement is rare but has been reported; ocular mucosal involvement specifically has not been reported. 8,9 Some data implicate activation of the JAK-STAT pathway with the development of LyP. A recent study of 12 patients with CD30 + lymphoproliferative disorders, including 6 LyP patients, suggested that an increased frequency of activating mutations in the JAK-STAT pathway may contribute to the pathogenesis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…7 Cutaneous periorbital and oral mucosal involvement is rare but has been reported; ocular mucosal involvement specifically has not been reported. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…PC-ALCL typically presents on head, neck, and extremities in immunocompromised patients as a rapidly growing solitary or localized group of nodules that may ulcerate. 8…”
Section: Discussionmentioning
confidence: 99%
“…PC-ALCL typically presents on head, neck, and extremities in immunocompromised patients as a rapidly growing solitary or localized group of nodules that may ulcerate. 8 The possibility of systemic ALCL must be considered in the evaluation of PC-ALCL. Our patient was assessed for systemic disease with PET/CT and underwent serial full-body skin exams for other cutaneous findings, both preoperatively for treatment planning, and postoperatively for surveillance of recurrent lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…ALK- ALCL involves the lymph nodes in ~50% of cases whereas extranodal involvement is less frequent [ 14 , 15 ]. Relatively common extranodal sites of involvement include the skin (excluding pc-ALCL), soft tissue, the liver and the lungs, whereas rare sites of involvement include the oropharynx, the gastrointestinal tract, the orbit, the brain, and the testes [ 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Skin lesions may be solitary or multiple in the form of papules, nodules, or tumors.…”
Section: Systemic Alk- Alclmentioning
confidence: 99%